2015
DOI: 10.1556/650.2015.30155
|View full text |Cite
|
Sign up to set email alerts
|

A sürgősségi ellátás új területe: az assistance orvostan

Abstract: A nemzetközi utazások száma a második világháború óta töretlenül növekszik. Az utazók igénye a biztonságra megnőtt, ennek ellenére utazás előtti tanácsadáson csak kevesen jelennek meg. Az utazók 50%-a valamilyen egészségügyi problémával találkozik útja során, és a biztosító segélynyújtó csoportja -az assistance szolgáltató -elrendezi, fi gyelemmel kíséri a külföldi betegellátást. A segélynyújtó csoportnál dolgozó orvosnak multidiszciplináris tudásanyaggal kell rendelkeznie a biztosítástechnikai és közegészségü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…This study demonstrated that emergent medical repatriation was considered one of the most important EMAS by travelers. Emergent medical repatriation is an interprofessional collaborative practice, which includes the field of emergency medicine and travel medicine [ 15 ]. Travelers are encouraged to apply for travel insurance to cover the possible health hazards that may arise during travel, especially when medical evacuation and repatriation are not covered by general health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that emergent medical repatriation was considered one of the most important EMAS by travelers. Emergent medical repatriation is an interprofessional collaborative practice, which includes the field of emergency medicine and travel medicine [ 15 ]. Travelers are encouraged to apply for travel insurance to cover the possible health hazards that may arise during travel, especially when medical evacuation and repatriation are not covered by general health insurance.…”
Section: Discussionmentioning
confidence: 99%